Purulent pericarditis and pericardiac tamponade in a pregnant hemodialysis patient: A case report. Issue 1 (22nd July 2015) - Adam, Fatma Ulku; Avci, Begum; Koc, Mevlut
Abstract: Bacterial pericarditis is rare in chronic hemodialysis and has poor prognosis. In this case, we report a pregnant hemodialysis patient who developed purulent bacterial pericarditis and pericardiac tamponade in the 28th week of her pregnancy, and who had delivered a healthy living baby.